How Congress Might Redesign a Leaner, Cleaner Writ of Habeas Corpus - Hoffstadt, Brian M. (2000)
In the last thirty years, the Supreme Court and Congress have made the federal writ of habeas corpus increasingly less available to state prisoners. By and large, they have restricted the writ through the creation and expansion of procedural barriers to federal habeas review. Recently, however, the policy debate over how to handle the deluge of federal habeas petitions has begun to shift away from creating procedural hurdles and toward a more straightforward narrowing of the substantive scope of the writ, as Congress has started to consider bills that would preclude state prisoners from raising certain federal constitutional claims in their habeas petitions. This Article examines how Congress might narrow the substantive scope of the writ of habeas corpus, should it ultimately decide to do so. The Article first considers the various criteria and the underlying theories of habeas that Congress might use to select the federal constitutional claims that would remain cognizable on habeas. The Article concludes that the best guide is a theory that accommodates both the historical role of habeas as a bulwark against fundamentally unfair incarceration and the current function of habeas as an additional appeal from state court. The Article then delineates which constitutional claims should remain available on habeas, and revisits the current procedural hurdles to see which may be eliminated or loosened. Finally, the Article briefly assesses the constitutionality of this new, narrower statutory writ